The Kurdish Satellite Channels' Coverage of Federal Government News - Hussein, Sundus AbdulWahab; Mohammad, Ammar Taher (ALBAHITH ALALAMI, 2024)
The research aims to examine how the two Kurdish-speaking satellite channels report on the federal government news and to identify the frameworks used by Rudaw and NRT news channels in their news bulletins. It also seeks to explore the type of content and the format of news coverage related to the federal government. The study employed partial content analysis, covering a period of three months to monitor federal government news broadcast before, during, and after the federal parliamentary elections on Rudaw and NRT.The research utilized a survey method, incorporating various techniques for data collection and analysis, including observation, interviews, and content analysis forms. The most significant findings of the research include:Kurdish satellite channels' interest in federal government news increases during crises or when specific gains are anticipated.The political news takes precedence in the treatment of federal government news in Kurdish satellite news bulletins.The two Kurdish-speaking channels differed in their approach to news reporting, with both focusing on "reports" as the main element in news bulletins.The two Kurdish satellite channels emphasize the technical format of news presentation, particularly the use of field reports and in-depth internal reports to convey information to viewers in a distinct manner compared to other technical formats.